Acne located on the trunk, whey protein supplementation: Is there any association? - Fatma Pelin Cengiz; Bengu Cevirgen Cemil; Nazan Emiroglu; Anil Gulsel Bahali; Nahide Onsun (Tabriz University of Medical Sciences, 2017)
Whey protein is a source of protein that was isolated from milk. Whey proteins are composed of higher levels of essential amino acids. The role of diet in acne etiology has been investigated for several years. It was established that milk and milk products can trigger acneiform lesions, and recent evidence supports the role of whey protein supplements in acne. Herein, we report 6 healthy male adolescent patients developing acne located only to the trunk after the consumption of whey protein supplements for faster bodybuilding. This is the first observation which specified the location of acneiform lesions among bodybuilders. In our opinion, a trendy and common health problem is beginning among adolescents in the gyms.